Free Senior High School Lunch Contributes to Dietary Quality of Nonresidential Students in Ghana. Issue 1 (March 2021) - Abizari, Abdul-Razak; Ali, Zakari; Abdulai, Seidu Alhassan; Issah, Fauzia; Frimpomaa, Nana Adwoa
Background: School feeding offers an excellent opportunity for targeted intervention to students not only as means for improving educational outcomes but also enhancing nutritional outcomes. The Government of Ghana introduced the free lunch feeding policy for nonresidential students in senior high schools (SHS) in 2018. Objective: We assessed unintended benefits of the free lunch program to dietary improvement. Methods: This was an analytical cross-sectional study among 403 (202 beneficiary and 201 non-beneficiary) students in SHS. The Food and Agriculture Organization's standard procedure for measuring dietary diversity score (DDS) was followed. A 3-day dietary recall was used to assess school day DDS, while a 24-hour recall was used to assess weekend DDS of students. Differences in DDS and food group consumption were determined using student t test and χ 2 test, respectively. Results: Nearly all (98.5%) beneficiary students consumed the free school lunch and 7 (70%) in 10 of them consumed it on all school days. While the students did not differ in their weekend meal DDS (6.3 ± 1.4 vs 6.5 ± 1.4, P = .39), beneficiaries of the school lunch had higher lunch DDS (7.5 ± 0.5 vs 6.5 ± 1.4, P < .001) and whole day DDS (11.5 ± 1 vs 9.3 ± 2.0, P < .001) compared to non-beneficiary students on school days. Even though the school lunch increased food group intake, vitamin-A rich vegetables and tubers, fruits, flesh and organ meats, and dairy products were hardly provided as components of school lunch. Conclusion: Provision of free school lunch meal to nonresidential students in SHSs in Ghana could contribute to improved diet quality.